Ellsworth Kelly - Austin - Kelly, Ellsworth (Radius Books, 2019)
In January 2015, the renowned American artist Ellsworth Kelly (1923-2015) gifted to the Blanton Museum of Art in Austin, Texas, the design concept for his most monumental work. A 2,715-square-foot stone building with luminous colored glass windows, a totemic wood sculpture and 14 black-and-white marble panels, the work is titled Austin, following the artist's tradition of naming particular works after the places for which they are destined. The structure is the only building the artist designed, despite Kelly's lifelong interest in architecture and architectural form dating back to his earliest window studies made while living in Paris in the 1940s. Envisioned by Kelly as a site for joy and contemplation, Austin is a cornerstone of the Blanton's permanent collection and a new icon for the city in which it stands. This comprehensive volume from Radius Books provides a thorough look at the project, from its first inception to its current position as one of the artist's most important and enduring works. An incisive essay by Carter E. Foster, deputy director of curatorial affairs at the Blanton Museum of Art, includes archival material, drawings, historic photographs and nearly all related works Kelly created as he developed the building's design